Menimbang kembali regulasi kawin hamil di Indonesia - Faisol, Syahid Akhmad; Hikmiyah, Hawa’ Hidayatul (Prodi Hukum Keluarga Islam Fakultas Syari'ah Universitas Islam Zainul Hasan Genggong Probolinggo, 2024)
This article aims to explore in depth the regulation of pregnant marriage in Indonesia in terms of the basic values of legal certainty, legal justice and legal benefits. Considering that since the enactment of this rule, it has caused turmoil in the community such as confusion over child guardianship and some people consider it a form of legalization of adultery. The method used is formative juridical with the main reference of Article 53 of the Compilation of Islamic Law, Law no. 1 of 1974 concerning Marriage and classical fiqh. The results of this research show that the establishment of regulation on pregnant marriage in Article 53 of the KHI prioritizes the value of benefit for women and their children by minimizing the harm caused. Then from the principle of legal certainty in the form of legality of pregnant marriage (Women adulteress) to determine the best choice, and legality of the law on the baby conceived in obtaining an equal position with other children. The principle of justice with the value of affirmative justice for the conceived child. As well as neminem non-laedere justice, a form of men's responsibility for actions that injure women. The principle of legal benefit by providing discretionary opportunities to practitioners in the Religious Courts and KUA to provide legal breakthroughs that are more actual and adaptive. Judging from the mashlahah mursalah the achievement of 4 out of 5 elements, namely the maintenance of religion by closing the path of unlawful acts, the maintenance of the soul with the survival of women and the baby they conceived, the maintenance of reason by maintaining the mental health of women and the growth and development of healthy babies.